A Contingent Resource‐Based Perspective of Supply Chain Resilience and Robustness. Issue 3 (July 2014) - Brandon‐Jones, Emma; Squire, Brian; Autry, Chad W.; Petersen, Kenneth J.
<x xml:space="preserve">Abstract</x> Understanding supply chain resilience and robustness is increasingly important for supply chain managers. This is due to the growing complexity of contemporary supply chains and the subsequent increased probability of experiencing a disruption. Few studies within the risk management literature have empirically disentangled the concepts of resilience and robustness or explored their antecedents. This study utilizes a contingent resource‐based view perspective to understand the relationship between specific resources (information sharing and connectivity), capabilities (visibility), and performance in terms of supply chain resilience and robustness. In addition, it utilizes supply base complexity as a moderating factor. Survey data collected from 264 UK manufacturing plants suggest that supply chain connectivity and information sharing resources lead to a supply chain visibility capability which enhances resilience and robustness. Of the four dimensions of complexity, only scale is found to have a strong moderating effect on this relationship, while geographic dispersion, differentiation, and delivery complexity do not have contingent effects. This study highlights theoretical and managerial implications for approaches to resilience and robustness.